From "Invented here" to "Use it everywhere!": A Learning health system from bottom and/or top? - Christian Colldén; Andreas Hellström (Wiley, 2022)
Abstract Introduction Departing from a practical problem of how to use digitalization to improve care quality and efficiency, this paper investigates how the concept of Learning Health Systems (LHSs) can be applied to an existing organization. LHSs offer a vision for how healthcare can accelerate both scale‐up of innovations and quality improvements at all levels. However, aligning stakeholders at different levels to convergent development is challenging and translation and adaptation of the LHS concept to fit with the existing organization is essential. Methods A one‐year longitudinal action research (AR) study was conducted within five psychiatric departments at the Sahlgrenska University Hospital in Gothenburg, Sweden. Translation of the LHS concept to the local circumstances within the organization was set as the aim, to both improve practice and further scientific understanding. An AR group led the practical and scholarly work and holistic data were collected, including field notes, documents, recordings, and workshops. Data were analyzed by an insider‐outsider approach. Results The one‐year study is described to provide insights into the process of designing a locally adapted LHS using an AR approach. Practical needs were identified and iteratively matched with theory to form a local LHS model. A conflict between top‐down and bottom‐up views on development emerged, where higher‐level management tended to prioritize uniform solutions and developers local learning. An adapted solution to balance these approaches was negotiated, consisting of a technical and an organizational part. Conclusions The conflict between top‐down and bottom‐up approaches for how to implement LHSs needs to be considered both in practical work to transform care organizations and in scientific studies of LHSs. The approach to translate, rather than instrumentally implement, LHSs to real‐world settings is suggested as advantageous. Furthermore, designing such endeavors as AR projects can provide excellent conditions to create LHSs that work in practice.